Challenges Imposed By Hypoglycemia in Adults With Type 1 Diabetes. (November 2019) - Martyn-Nemeth, Pamela; Duffecy, Jennifer; Fritschi, Cynthia; Quinn, Laurie
Little is known regarding how hypoglycemia and associated fears influence day-to-day life among adults with type 1 diabetes (T1DM) who use contemporary diabetes management strategies. To address this gap, we performed an exploratory qualitative study with five focus groups of 30 people aged 20 to 57 years with T1DM. Sessions were audiotaped and transcribed, and then analyzed. Eight themes emerged: (a) hypoglycemic worry, (b) unpredictability and loss of control, (c) contending with life stress, (d) exercise benefits and challenges, (e) a changed relationship with food, (f) sleep fears, (g) a love/hate relationship with technology, and (h) coping strategies to make it better. Fear of hypoglycemia, diabetes management, and work demands confer a high degree of stress. Challenges surround food, exercise, and sleep. Technology is important but does not relieve fear of hypoglycemia. Developing strong coping skills and creating a safety net of support are necessary.